Plate Fixation versus Arthroscopic‐Assisted Plate Fixation for Isolated Medium‐Sized Fractures of the Greater Tuberosity: A Retrospective Study. Issue 5 (18th October 2020) - Sun, Qi; Ge, Wei; Li, Gen; Wu, Jie Zhou; Lu, Guanghua; Li, Runmin; Zhao, Zhenyu; Zhu, Yaru; Xu, Youzhi; Wang, Lei; Cai, Ming
Abstract : Objectives: To compare the clinical outcomes of plate fixation and arthroscopic‐assisted plate fixation in patients with displaced isolated medium‐sized fractures of the greater tuberosity. Methods: From July 2013 to October 2017, patients with displaced isolated medium‐sized fractures of the greater tuberosity who underwent arthroscopic‐assisted plate fixation (ASPF group) or open reduction and internal plate fixation (ORIF group) were retrospectively reviewed and analyzed. There were 19 patients in the ASPF group and 27 patients in the ORIF group, with comparable demographic characteristics. The average age of patients was 49.4 ± 12.1 years in the ASPF group and 46.9 ± 11.4 years in the ORIF group. The shoulder function reflected by the Constant–Murley (CS) scores, the American Shoulder and Elbow Surgeons (ASES) scores, and the range of motion (ROM) in the both groups at the last follow‐up were analyzed in the study. Surgery time, postoperative pain, and postoperative complications were also reviewed. Results: A total of 46 eligible patients were included in this study. The mean follow‐up was similar for the ASPF (19.4 ± 3.7 months) and the ORIF (18.2 ± 3.2 months) groups ( P = 0.372). All patients had achieved primary incision healing in both groups at the last follow‐up. The surgery time was 96.8 ± 11.7 min and 64.2 ± 8.3 min in the ASPF group and the ORIF group, respectively ( P < 0.01). All the CS scores ( P = 0.278), ASES scores ( P = 0.426), and ROM were slightly better in the ASPF group than in the ORIF group, but they did not attain significant differences. In addition, there was no significant difference in the postoperative complication rate between the ASPF group (10.5%) and the ORIF group (18.5%) ( P = 0.522). In the ASPF group, there was only one patient with postoperative shoulder stiffness and one case of fracture malunion. In the ORIF group, there were two cases of postoperative shoulder stiffness, two cases of fracture malunoin, and one case of subacromial impingement. Other major postoperative complications, such as fracture nonunion, pullout of the suture anchor, and screw penetration, were not observed in either group. Conclusion: Arthroscopic‐assisted plate fixation is effective and may be an alternative in the treatment of displaced isolated medium‐sized fractures of the greater tuberosity. Abstract : Schematic illustration of the anchor insertion, suture tightening, and plate fixation.